Specificity of working with gifted primary school students in China - Stanislav Naumenko (Journal of Education, Health and Sport, 2020)
In China, a Key National Strategy has been developed. According to the Strategy, education is refocused on high quality, the development of a holistic approach to the harmonious development of pupils' personalities, which should be imbued with the spirit of innovation, business skills and develop moral, intellectual, physical, and aesthetic aspects. The Ministry of Education of China also supported the position of an individual approach to each pupil and considering his physical and psychological development. The reform aims to create a favorable educational environment for the development of each pupil, active research training, increasing the flexibility and diversity of courses. Among all the subjects of the educational program, literacy is defined as the most fundamental for the successful assimilation of other educational areas and the holistic development of children's personalities, an indispensable strategy for preserving cultural heritage, national unity, and creativity. The program defined the principles of training. They are: to involve all pupils in the educational process and develop their intellectual abilities, to understand the peculiarities of language and literature education, to promote independent learning, joint learning, and learning based on pupils' requests, to take into account their differences and learning needs, to create curricula based on openness and viability. Such positive changes in pedagogical practice create a favorable educational environment that adapts to different rates of pupil learning. The program aims to develop a wide range of pupils' skills, such as literary literacy, financial literacy, mathematical literacy, and scientific literacy. The program provides an inclusive educational environment that can engage gifted pupils in terms of pedagogical strategies (e.g., individualized learning, research learning, and independent learning), enriched reading materials, and dynamic, multiple assessments). The main problems of implementing the new literacy program are: insufficient teacher competence, the difficulty of transforming deep traditions from the pedagogy of transmission and collectivism to the pedagogy of constructivism, the large class size in China leads to overload of teachers.